PENINGKATAN KESADARAN MASYARAKAT DESA PARUNGSEAH TERHADAP BENCANA MELALUI PROGRAM EDUKASI DAN PELATIHAN MITIGASI BENCANA - Alif Deva Azharry H.A.G; Muhammad Arya Sidiq; Jilan Madyan; Silfanny Siti Rahma; Citra Asterina; Eneng Yeni (LPPM Politeknik Pajajaran ICB Bandung, 2023)
Public knowledge and awareness about disasters is very important in efforts to reduce the risks and losses caused by natural disasters. In this study, we explain the implementation of the Education and Training Program to increase public awareness of disasters. This program is designed to provide basic knowledge about the types of disasters that may occur in the area, early warning signs, evacuation procedures, and first aid measures in disaster situations. We collaborate with local governments, educational institutions, and community organizations to deliver this program to the community. The method used in this research is counseling and interactive training. We conduct counseling sessions in various locations such as schools, community centers, and community group meetings. In addition, we also carry out practical skills training such as simple fire fighting, first aid, and emergency evacuation